Key Player in Cardiac Hypertrophy, Emphasizing the Role of Toll-Like Receptor 4 - Xiao, Zheng; Kong, Bin; Yang, Hongjie; Dai, Chang; Fang, Jin; Qin, Tianyou; Huang, He (Frontiers in Cardiovascular Medicine, 2020)
Toll-like receptor 4 (TLR4), a key pattern recognition receptor, initiates the innate immune response and leads to chronic and acute inflammation. In the past decades, accumulating evidence has implicated TLR4-mediated inflammatory response in regulation of myocardium hypertrophic remodeling, indicating that regulation of the TLR4 signaling pathway may be an effective strategy for managing cardiac hypertrophy's pathophysiology. Given TLR4's significance, it is imperative to review the molecular mechanisms and roles underlying TLR4 signaling in cardiac hypertrophy. Here, we comprehensively review the current knowledge of TLR4-mediated inflammatory response and its interaction ligands and co-receptors, as well as activation of various intracellular signaling. We also describe the associated roles in promoting immune cell infiltration and inflammatory mediator secretion, that ultimately cause cardiac hypertrophy. Finally, we provide examples of some of the most promising drugs and new technologies that have the potential to attenuate TLR4-mediated inflammatory response and prevent or reverse the ominous cardiac hypertrophy outcomes.